Some New Variants of Cauchy's Methods for Solving Nonlinear Equations - Tianbao Liu; Hengyan Li (Journal of Applied Mathematics)
We present and analyze some variants of Cauchy's methods free from second derivative for obtaining simple roots of nonlinear equations. The convergence analysis of the methods is discussed. It is established that the methods have convergence order three. Per iteration the new methods require two function and one first derivative evaluations. Numerical examples show that the new methods are comparable with the well-known existing methods and give better numerical results in many aspects.